Exploring vestibular stimulation to reduce the influence of cybersickness on virtual reality experiences - Smith, Shamus P.; Nalivaiko, Eugene; Owen, Sam; Depireux, Didier; Flynn, Mark (Frontiers in Virtual Reality, 2025)
IntroductionThere is increasing use of head-worn displays to support immersive virtual reality (VR) experiences. However, users of such technology often encounter motion sickness-like effects, commonly termed cybersickness. The unpleasant effects of cybersickness can limit the duration of VR technology usage and deter return use after only one bad experience. One explanation of cybersickness is that it is a physiological responses to perceived differences between the visual and vestibular stimulation provided via VR technology and the user’s current body positioning and movement, i.e., a mismatch between visual and vestibular senses.MethodsAn exploratory user study is described that investigates the use of technology to influence vestibular cues and change experiences of cybersickness. A vestibular stimulation device using bone conduction was applied to users experiencing cybersickness induced by a VR roller-coaster in a head-worn display. Three conditions were tested: a control group without the device and two groups with the device configured to different vibration force levels.ResultsResults showed that users with the stronger vibration level, when compared to a control group, had different virtual environment experiences with longer ride durations and lower reported nausea scores.DiscussionAlthough limited by participant numbers, the results are promising for applying vestibular stimulation to positively influence cybersickness experiences in head-worn displays. Given the spreading application of VR technologies and the need to mitigate cybersickness, there is a need to further evaluate the efficacy of such devices.